Hydrogen adsorption capacity investigation of Ni-Co-Al mixed oxides - Salam, M.A. (Trans Tech Publications Ltd, 2014)
Micro-mesoporous mixed oxides containing nickel, cobalt and aluminum have been synthesized using conventional coprecipitation method. FESEM and HRTEM analyses demonstrated the flower and hexagonal plate-like nano-structured of mixed oxides. Different mixed oxide formation, homogenous metal dispersion, textural properties were investigated using XRD, ICP-MS and BET (N2 adsorption-desorption) techniques. Nano-structured mixed oxides exhibited 2.6 wt hydrogen adsorption that were studied using temperature programmed reductionadsorption- desorption (H2-TPR/TPD) and thermogravimetric and differential thermal analysis (TGA-DTA) techniques. Investigation corresponds that morphologies, textural properties and surface energy of mixed oxides are important in hydrogen adsorption. Â© (2014) Trans Tech Publications, Switzerland.